2020
DOI: 10.3389/fcimb.2020.00207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Toxoplasma gondii Oocyst Phagocytosis by Macrophages

Abstract: Oocysts are the environmentally resistant stage of the protozoan parasite Toxoplasma gondii. They are responsible for foodborne infections in humans and animals worldwide. Infectious oocysts contain sporozoites that have to exit the sporocyst and oocyst walls to initiate replication of the parasite within the host tissues. Given their robustness and resistance to chemical degradation, it is still unclear how the oocyst and sporocyst walls release the sporozoites. This process called excystation is thought to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Many proinflammatory agents are generated during early and acute T. gondii invasion, and, largely, cytokines are released. Cytokine IFN-γ can efficiently activate M1 macrophages through the NF-κB signaling pathway and promote M1 macrophages to secrete proinflammatory cytokines (IL-1β, TNF-α, IL-6, and IL-23), inducible nitric oxide synthase (iNOS), and nitric oxide (NO), even enhancing the ability of phagocytes to resist T. gondii [ 23 , 24 ]. Interestingly, although macrophages play an important role in resisting the replications of T. gondii [ 25 ], T. gondii has developed multistrategies to limit the antimicrobial activities of macrophages [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many proinflammatory agents are generated during early and acute T. gondii invasion, and, largely, cytokines are released. Cytokine IFN-γ can efficiently activate M1 macrophages through the NF-κB signaling pathway and promote M1 macrophages to secrete proinflammatory cytokines (IL-1β, TNF-α, IL-6, and IL-23), inducible nitric oxide synthase (iNOS), and nitric oxide (NO), even enhancing the ability of phagocytes to resist T. gondii [ 23 , 24 ]. Interestingly, although macrophages play an important role in resisting the replications of T. gondii [ 25 ], T. gondii has developed multistrategies to limit the antimicrobial activities of macrophages [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It results in induction of the cellular phagocytosis machinery, generation of reactive oxygen species, and inflammasome activation ( 63 ). Previous in vitro studies showed that oocysts are taken up by a mouse macrophage cell line in a phagocytic manner, and evidence was provided for subsequent oocyst wall rupture and occasional sporozoite release and intracellular differentiation into tachyzoites ( 64 , 65 ). Freppel et al speculated that oocyst phagocytosis might be a way of parasite dissemination in the host if similar processes with inhaled oocysts would occur in alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 21% of waterborne toxoplasmosis outbreaks between 1976 and 2009 were derived from oocysts [ 10 , 17 ]. Disappointingly, the mechanism of the unclosing of the oocyst walls that is triggered by digestive agents, followed by the release of sporozoites from oocysts in the small intestine is still unclear [ 10 , 18 ]. Heather et al first identified the profile of the proteome of sporulated oocyst walls and sporocysts/sporozoites, as well as an inventory of oocyst inner wall proteins and outer wall proteins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%